ENGINEER WP2 SS1 UAV DJI MAVIC - Barazzetti, Luigi; Cuca, Branka; Oreni, Daniela; Previtali, Mattia; Hadjipetrou, Stylianos; Agapiou, Athos (My University, 2024)
This dataset was created during ENGINEER project activities and is accessible only upon user request and approval by the responsible national authority of Cyprus, namely the Department of Antiquities. The dataset pertains to images acquired at the tombs of the kings using a DJI Mavic.